Analisis Pengaruh Infrastruktur, Tingkat Kemiskinan dan Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi Provinsi Bali 2015-2020 - Risthi Khoirunnisa Wadana; Whinarko Juli Prijanto (CV. Syntax Corporation Indonesia, 2021)
Economic growth is an important pillar in regional development. Economic growth is one of the indicators to measure development outcomes and is an important indicator to determine the direction of future development. If the infrastructure is not good, development will not run smoothly. If infrastructure is weak, the economic operations of a country or region will be inadequate. And humans are not only the object of development, but are also expected to be the main body, making useful contributions to the progress of an area from a macro perspective. The development of the rate of economic growth in the Province of Bali during the 2015-2020 period experienced fluctuating changes. Therefore, this study aims to determine the effect of economic variables on the economic growth of districts/cities in the province of Bali. The type of data in this study is panel data which is a combination of time series data from 2015-2020 and cross section data from nine districts/cities in Bali Province. By using Eviews X software, panel data regression analysis in this study uses the Fixed Effect Model approach, based on the results of the study it was obtained that partially road infrastructure variables have a positive and significant influence on the rate of economic growth. Meanwhile, the variable of the poor population partially has a positive but not significant effect on the rate of economic growth. And partially the Human Development Index (HDI) variable has a negative and significant influence on the rate of economic growth